Identification of Genetic Variants for Female Obesity and Evaluation of the Causal Role of Genetically Defined Obesity in Polycystic Ovarian Syndrome - Ahn Y (Dove Medical Press, 2020)
Yeongseon Ahn,1 Hyejin Lee,2 Yoon Shin Cho1 1Department of Biomedical Science, Hallym University, Chuncheon, Gangwon-do, Republic of Korea; 2Department of Internal Medicine, Ewha Womans University School of Medicine, Seoul, Republic of KoreaCorrespondence: Yoon Shin ChoDepartment of Biomedical Science, Hallym University, Chuncheon, Gangwon-do 24252, Republic of KoreaTel +82-33-248-2111Fax +82-33-256-3420Email yooncho33@hallym.ac.krPurpose: Observational studies have demonstrated an increased risk of polycystic ovarian syndrome (PCOS) in obese women. This study aimed to identify genetic variants influencing obesity in females and to evaluate the causal association between genetically defined obesity and PCOS in Korean women.Methods: Two-stage GWAS was conducted to identify genetic variants influencing obesity traits (such as body mass index [BMI], waist–hip ratio [WHR], and waist circumference [WC]) in Korean women. Two-sample Mendelian randomization (MR) analysis was employed to evaluate the causal effect of variants as genetic instruments for female obesity on PCOS.Results: Meta-analysis of 9953 females combining discovery (N = 4658) and replication (N = 5295) stages detected four (rs11162584, rs6760543, rs828104, rs56137030), six (rs139702234, rs2341967, rs73059848, rs5020945, rs550532151, rs61971548), and two genetic variants (rs7722169, rs7206790) suggesting a highly significant association (P < 1× 10− 6) with BMI, WHR, and WC, respectively. Of these, an intron variant rs56137030 in FTO achieved genome-wide significant association (P = 3.39× 10− 8) with BMI in females. Using variants for female obesity, their effect on PCOS in 946 cases and 976 controls was evaluated by MR analysis. MR results indicated no significant association between genetically defined obesity and PCOS in Korean women.Conclusion: This study, for the first time, revealed genetic variants for female obesity in the Korean population and reported no causal association between genetically defined obesity and PCOS in Korean women.Keywords: female obesity, polycystic ovarian syndrome, causal relation, genome-wide association study, Mendelian randomization